한국의 뿔제비갈매기(Thalasseus bernsteini) 도래 시기와 번식 현황 - 이윤경(Yunkyoung Lee); 김우영(Wooyoung Kim); 강지현(Jihyun Kang); 유성연(Sung-Yeon Yoo); 차현기(Hyoun-Gi Cha); 이상연(Sang-Yeon Lee); 노두리(Doory No) (한국조류학회지, 2021)
뿔제비갈매기는 전세계 생존하는 개체수가 약 100마리로 추정되는 국제적인 멸종위기종(IUCN Redlist CR)이며, 2000년 이후, 알려진 번식지는 중국(대만) 해안의 4개 섬에 불과했다. 국내에 기록된 적이 없던 뿔제비갈매기는 2016년 4월 괭이갈매기 집단번식지인 육산도(칠산도의 부속섬)에서 최초로 발견되었다. 본 연구는 5년간(2016-2020) 뿔제비갈매기의 도래 패턴과 번식 현황을 파악하기 위해서 수행되었다. 육산도에서 확인된 뿔제비갈매기 개체수는 2016년 5마리에서 2020년 8마리로 점차 증가하였다. 이들은 대부분 짝을 이루어(때로는 단독으로) 비동시적으로 번식지에 도착했는데, 첫 번째 개체(또는 짝)의 도래일은 2018년에 3월 29일, 2019년에 3월 30일, 2020년에 3월 21일이었다. 뿔제비갈매기는 산란 전까지는 주로 밤 시간대에만 섬에서 머물렀고, 산란 하루 전날부터 낮에도 섬에서 관찰되었다. 뿔제비갈매기의 첫 번째 산란일은 2018년과 2019년 4월 18일, 2020년 4월 19었다. 도래한 개체들 중에서 매년 한 쌍(2019-2020)에서 두 쌍(2016-2018)만이 번식을 시도하였다. 우리는 5년간 재번식 둥지를 포함하여 총 11개의 산란한 둥지를 확인하였는데, 이 중에서 4개의 둥지에서 새끼가 이소하였고, 나머지 7개 둥지는 포란기간과 육추 초반에 실패하였다. 실패 원인은 번식 개체의 미숙한 행동(둥지를 안정적으로 만들지 못하고, 알을 잘 품지 못해 노출시킴)과 괭이갈매기와의 싸움 및 공격으로 확인되었다. 실패한 개체는 10일, 12일만에 재산란을 하였다. 뿔제비갈매기의 한배산란수는 1개, 포란기간은 26-28일이었다. 새끼는 부화한지 37-43일에 부모와 함께 비행을 하였다. 본 연구결과는 세계적으로 희귀한 뿔제비갈매기 번식에 대한 기초자료를 제공하며, 지속적인 연구 결과를 토대로 종과 서식지 보전 전략수립에 활용할 수 있을 것으로 기대된다. The Chinese Crested Tern (Thalasseus bernsteini) is a critically endangered species according to IUCN Red List, with an estimated global population of approximately 100 individuals. Since 2000, only four islands off the coast of China and Taiwan had been recognized as the breeding habitats of these terns. In April 2016, this species was recorded for the first time in Korea on the Yuksan Islet (one of the islets in the Chilsan Islands)-an important breeding ground for the Black-tailed Gull (Larus crassirostris). Here, we studied the arrival pattern and breeding status of Chinese crested terns over for 5 years (2016-2020). The number of individuals gradually increased from five in 2016 to eight in 2020. The terns arrived at the breeding site in pairs (or sometimes alone) and asynchronously. The first individuals were identified on March 29, 2018; March 30, 2019; and March 21, 2020. The terns only stayed on the island during the night until laying eggs. The first eggs were recorded on April 18 in 2018 and 2019, and on April 19 in 2020. One pair during 2019-2020 and two pairs during 2016-2018 attempted breeding. During the 5 years, we identified 11 breeding nests, including the replacement eggs, but chicks successfully fledged from only four of these. In the remaining nest, breeding failed during the egg incubation period (n=6) or at the early stage of the chick-rearing period (n=1). The causes of failure were poor breeding behaviors (building poor-quality nests and exposing eggs during incubation), and harassment by Black-tailed Gulls. These terns laid a replacement egg 10 to 12 days after the failure. Clutch size was one (n=11), and the incubation period was 26-28 days. The chicks flew with the parents 37 to 43 days after hatching. Our findings offer fundamental data on the breeding of Chinese crested terns and are crucial to establish conservation strategies for this species and its habitat. KCI Citation Count: 0